Condition factor, catch per unit effort, environmental condition and migratory pattern of Thynnichthys thynnoides (Bleeker, 1852) for fisheries management at Rui River, Perak, Malaysia - Amonodin, Mohamad Radhi (2017)
This study had been carried out to find out the condition factor, environmental condition and migratory pattern of tiny scale barb Thynnichthys thynnoides in the Rui River, Gerik, Perak. Eight sampling sites were chosen and located in the main channel of the Perak River and its tributary, Rui River, comprising the upstream, middle stream and lower stream of the river system. The water quality parameters were determined by using the standard methods. Thynnichthys thynnoides were captured between May and October 2015 by using two fishing gears consisting four sets of gill net with various mesh sizes (2.5, 5.0, 7.6 and 10.0 cm) and a scoop net. A total of 238 individuals of T. thynnoides were collected during this study with mean total length (TL) of 18.95 ± 2.48 cm and weight of 63.39 ± 20.05 g. Catch per Unit Effort (CPUE) escalated in October (7.75/scoop/hour) compared to September (2.05/scoop/hour) indicated the peak migration month of this species. Growth parameters (a = 0.00824, b = 3.0238, R2 = 0.9448) of T. thynnoides derived from logarithmic relationship between body weight (g) and total length (cm) indicated an isometric growth. Overall water quality parameters do not have significant variance between spawning and non-spawning seasons except for turbidity (F = 13.23, p < 0.05). Despite Rui River was polluted with suspended particles with mean TSS concentration of 77.2 mg/L during spawning season, T. thynnoides still migrate to upper stream of Rui River. Habitat assessment scoring indicated that physical habitat structure of Rui River fell into suboptimal category which most likely able to support fish population and thus provide suitable habitat for T. thynnoides during spawning season. Conclusively, it was observed that T. thynnoides population was dependent with environmental conditions.